2023
DOI: 10.1540/jsmr.59.1
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal in gastrointestinal inflammatory diseases

Abstract: The gastrointestinal (GI) tract is a vital organ that digests food, absorbs nutrients, and excretes waste. Normal GI motility is the basis for these functions. The interstitial cells of Cajal (ICC) in the GI muscularis layer promote GI motility together with the enteric nervous system and smooth muscle cells. Since GI motility results from complex coordination of these heterogeneous cells, failure of any one of them can lead to GI dysmotility. Knowledge about ICC in physiological conditions has accumulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…This interaction could pro-https://doi.org/10.17221/2/2024-VETMED mote eosinophil adherence and initiate stimuli for eosinophil migration into inflamed tissues (Oliveira et al 2002). Consequently, although the c-Kit was initially positive in the early FGESF, c-Kit results may become negative as fibrosis and inflammation progress (Kaji and Hori 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction could pro-https://doi.org/10.17221/2/2024-VETMED mote eosinophil adherence and initiate stimuli for eosinophil migration into inflamed tissues (Oliveira et al 2002). Consequently, although the c-Kit was initially positive in the early FGESF, c-Kit results may become negative as fibrosis and inflammation progress (Kaji and Hori 2023).…”
Section: Discussionmentioning
confidence: 99%
“…2002 ). Consequently, although the c-Kit was initially positive in the early FGESF, c-Kit results may become negative as fibrosis and inflammation progress ( Kaji and Hori 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with STC in China is increasing annually, and the prevalence rate of STC is approximately 3.19–11.6% ( Bharucha and Lacy, 2020 ; Yao et al, 2022 ). Various factors such as Cajal’s interstitial cells, immune factors, endocrine factors, laxatives, psychological factors, diet, and exercise habits have been implicated in the onset and exacerbation of STC ( He et al, 2000 ; Lyford et al, 2002 ; Wedel et al, 2002 ; Foong et al, 2020 ; Serra et al, 2020 ; Wang H. et al, 2022 ; Kaji and Hori, 2023 ). An increasing number of studies have shown that gut microbiota and neurotransmitters are closely related to STC ( Ding et al, 2018 ; Ohkusa et al, 2019 ; Göthert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly referred to as the “pacemaker cells” of the gastrointestinal tract ( 8 ). Research has shown that ICC display distinct functionalities across different subtypes ( 9 ). Intramuscular interstitial cells (ICC-IM) modulate neurotransmitter responses ( 10 ), and myenteric interstitial cells (ICC-MY) serve as pacemakers by generating slow waves that influence smooth muscle contractions ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, submucosal interstitial cells (ICC-SM) coordinate the regulation of secretions and reflexes within the mucosal and submucosal layers ( 12 ), while septal interstitial cells (ICC-SEP) function as a supportive network, maintaining the structural integrity of the gastrointestinal wall ( 13 , 14 ). However, as time passes, the complexity and diversity of ICC research have steadily increased, extending to multiple systems, such as the nervous, digestive, and urinary systems, among others ( 9 , 15 , 16 ). Consequently, there is a need for a comprehensive methodology to fully understand their developmental trajectories and impact.…”
Section: Introductionmentioning
confidence: 99%